Women and entrepreneurship : a case study of Portugal / Anabela Dinis and Marilyn Helms - Dinis, Anabela; Helms, Marilyn (Faculty of Business and Management ; UiTM Press, 2000)
From the theoretical point of view, this study explores the mechanisms of the creation and development of business by women in Portugal. The study also compares the Portuguese entrepreneurial processes of women, where this trend is only emerging, to results obtained in other parts of the world. It explains both "why" and "how" women create and develop their businesses. Following a literature review about women entrepreneurs in Portugal, specific aspects and characteristics of their businesses, their motivations and their challenges, are discussed. Also the issue of institutional support is reviewed. At the practical level, these findings represent an indicator for politicians and officials responsible for the regional development of public support structures necessary to support entrepreneurship. This could help to maintain or improve the lines of support and adapt local development strategies to the female entrepreneur's characteristics. Finally the conditions of current women and future women entrepreneurs in Portugal is explored.